2017
DOI: 10.1016/j.jcrs.2016.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of resident training and preparedness for cataract surgery

Abstract: Educational resources, such as surgical simulators and supervised wet labs, tended to be associated with greater resident-perceived competency for steps in cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 3 publications
2
10
1
Order By: Relevance
“…Practice labs are one such example, of an educational resource that can be used to provide residents with hands-on training in a low-stress environment and help develop their surgical skill set, while promoting surgical confidence. Multiple studies have, in fact, reported on the utility of such training in preparing residents for the OR 9. A similar trend was also observed in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Practice labs are one such example, of an educational resource that can be used to provide residents with hands-on training in a low-stress environment and help develop their surgical skill set, while promoting surgical confidence. Multiple studies have, in fact, reported on the utility of such training in preparing residents for the OR 9. A similar trend was also observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Recent years have seen a rapid growth in surgical teaching resources available to ophthalmology residency programs. Utilization of these training resources has been shown to correlate with increased levels of resident preparedness and competence for cataract surgery 9. We believe that the proper use of these resources can similarly help residents prepare for open globe repair.…”
Section: Introductionmentioning
confidence: 87%
“…This concept was corroborated by two of our trainees having radial extensions of their CCC when eye movements were introduced. Several studies have shown improved performance of junior ophthalmologists in the operating room after practicing on the Eyesi [12][13][14][15][16][17][18][19][20][21][22]; in particular, the rates of errant CCC are significantly reduced [17, 19,]. One of the limitations of the Eyesi in preparing trainees for real cataract surgery, however, is lack of intraoperative eye movement during the exercises.…”
Section: Discussionmentioning
confidence: 99%
“…12 Finally, Puri et al highlighted increased selfperceived competency among residents with access to either VRS or wet laboratory training in a large cohort spanning numerous training programs. 25 Simulation as an Assessment Tool (►Table 3)…”
Section: Qualitative Assessment Of Satisfaction and Preparednessmentioning
confidence: 99%
“…Rather, they found the element of faculty supervision, discussion, and feedback to be most integral to development of proper techniques and comfort level. 25…”
Section: Negative Findingsmentioning
confidence: 99%